2012
DOI: 10.3199/iscb.7.117
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Studies in Cosmos sulphureus Cav.

Abstract: ABSTRACT. Cosmos sulphureus Cav. was studied with respect to its meiotic behavior. It has been observed that this plant species is a diploid with the chromosome number of n=12. The course of meiosis was normal in most of the cells but some meiotic irregularities have also been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Cosmos sulphureus, one of them used traditionally as anthelmintic in Cameroon. It is a plant belonging to the Asteraceae family, commonly known as yellow cosmos spread throughout India, Florida, Southern United States and South America [14]. This plant is generally used for improving blood circulation, antiaging agent, reducing body heat, strengthening bone marrow and to treat infections associated with pathogenic microorganisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmos sulphureus, one of them used traditionally as anthelmintic in Cameroon. It is a plant belonging to the Asteraceae family, commonly known as yellow cosmos spread throughout India, Florida, Southern United States and South America [14]. This plant is generally used for improving blood circulation, antiaging agent, reducing body heat, strengthening bone marrow and to treat infections associated with pathogenic microorganisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…The height of the plant is 90-120 cm and has compound leaves. Flowering season is October to December [15]. The present study was undertaken to investigate the phytochemical and antioxidants properties of bark peel extract of Araucaria columnaris and flower extracts of Cosmos sulphurous with a view to assess the potentials of both the plants as a source for phenolic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…This is not due to low haploid number (n=8) but to chromosome length. The frequency of chiasma differences were extensively analyzed in several taxa belonging to Asteraceae (Ghaffari & Djavadp, 1998;Gupta et al, 2013;Kumari &Sidhu, 2012 andSheidai et al, 2006). They concluded that the cytotaxonimic features verify the affinity of the related taxa of Asteraceae.…”
Section: Cotula Barbatamentioning
confidence: 99%